2015
DOI: 10.18632/oncoscience.137
|View full text |Cite
|
Sign up to set email alerts
|

MiR-148a, a microRNA upregulated in the WNT subgroup tumors, inhibits invasion and tumorigenic potential of medulloblastoma cells by targeting Neuropilin 1

Abstract: Medulloblastoma, a common pediatric malignant brain tumor consists of four molecular subgroups viz. WNT, SHH, Group 3 and Group 4. MiR-148a is over-expressed in the WNT subgroup tumors, which have the lowest incidence of metastasis and excellent survival among all medulloblastomas. MiR-148a was expressed either in a transient manner using a synthetic mimic or in a stable doxycycline inducible manner using a lentiviral vector in non-WNT medulloblastoma cell lines. Expression of miR-148a to levels comparable to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 45 publications
1
23
0
Order By: Relevance
“…Cao et al showed also that the knockdown of NRP-1 by short hairpin RNA reduced migration and invasion of renal carcinoma cells [ 13 ] which was also found in our results with a decrease of invasion ability of MB stem cells after exposure to MR438. In the same way, it was recently shown that MiR-148a, a MiRNA which decreased NRP-1 expression, also inhibited invasion and tumorigenic potential of MB cells in the WNT subgroup [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cao et al showed also that the knockdown of NRP-1 by short hairpin RNA reduced migration and invasion of renal carcinoma cells [ 13 ] which was also found in our results with a decrease of invasion ability of MB stem cells after exposure to MR438. In the same way, it was recently shown that MiR-148a, a MiRNA which decreased NRP-1 expression, also inhibited invasion and tumorigenic potential of MB cells in the WNT subgroup [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this, our results show that miR-148a suppresses breast cancer metastasis possibly through down-regulation of WNT1. NRP1 has recently been identified as a target gene of miR-148a in medulloblastoma [ 52 ]. In breast cancer, several studies have implicated NRP1 in various aspects of cell growth, survival, migration, and metastasis [ 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…In 2013, the same authors confirmed the effectiveness of miRNA-based molecular subgrouping on additional 103 MBs, including 59 formalin-fixed paraffin-embedded tissues (Kunder et al, 2013). Later on, miR-449a (Li et al, 2016) and miR-148a (Yogi et al, 2015) were reported as candidate tumor-suppressor genes and potential diagnostic markers or therapeutic targets in WNT-MBs.…”
Section: Mirna Profiling As a Tool For Mb Diagnosis And Stratificationmentioning
confidence: 90%